(untitled) (Archive of Conferences, 2021)
This professional dedication and professional compliant focus on psychology as the subject of learning. The article also describes professional self-sacrifice, professional competence, its theoretical foundations, and the meaning of foreign and local research. The text of the article was written in the scientific literature presented in the application and their analysis